The Impact of Government Policies and Micro, Small, and Medium Enterprises (MSME) Empowerment on the Development of the Coffee Processing Industry: A Case Study of Banda Aceh - Nasri Zarman; Eliana; Muhammad; Yahya (Universitas Pelita Harapan, 2025)
This study examines the impact of government policy and micro, small, and medium enterprises (MSMEs) empowerment on the development of the coffee processing industry in Banda Aceh, Indonesia. Using a quantitative approach with a sample of 30 coffee MSMEs, data were collected through surveys and interviews, and analyzed with multiple regression. The results reveal that government policy, including training, equipment assistance, and licensing facilitation, has a significant positive effect on industry development, although challenges remain in financing access and equitable support. Similarly, MSME empowerment, particularly in human resource capacity building and managerial guidance, also demonstrates a significant positive effect, yet programs tend to be short-term and lack sustainability. Simultaneously, both variables explain 53.2% of the variation in industry development, while the rest is influenced by factors such as market access, innovation, and local coffee culture. This study highlights the crucial role of adaptive government policy and continuous MSME empowerment in fostering a competitive and sustainable coffee industry in Banda Aceh.